The life cycle of malnutrition: IFPRI 1999-2000 Annual Report Essay - Gillespie, Stuart; Flores, Rafael (International Food Policy Research Institute, 2000)
This year some 30 million babies in the developing world—around 82,000 every day—will be born with impaired growth due to poor nutrition during fetal life. term. The authors examine each stage of the life cycle, from birth and infancy to childhood, adolescence, adulthood, and old age. In developing countries the main direct causes of intrauterine growth retardation (IUGR) are nutritional. IUGR infants are more likely to become stunted children. Data on the nutritional status of school-age children are increasingly being collected, as evidence mounts linking malnutrition or hunger with poor school attendance, performance, and learning. The economic livelihood of populations depends on the health and nutritional well-being of adults. Recent multicountry studies have shown significant malnutrition among older adults. Vicious circles—such as the life cycle of malnutrition—based as they are on mutually reinforcing processes, can be transformed into virtuous circles by more consistently and effectively applying our growing knowledge of what works, and where, in combating malnutrition. While preventing fetal and early childhood malnutrition deserves particular attention, the life cycle dynamics of cause and consequence demand a holistic, inclusive approach to malnutrition. Adequate nutrition is a human right for all people, and intervening at each point in the life cycle will accelerate and consolidate positive change.